1995
DOI: 10.1152/ajpcell.1995.268.2.c389
|View full text |Cite
|
Sign up to set email alerts
|

Permeation and gating properties of a cloned renal K+ channel

Abstract: The renal K+ channel (ROMK2) was expressed in Xenopus oocytes, and the patch-clamp technique was used to assess its conducting and gating properties. In cell-attached patches with 110 mM K+ in the bath and pipette, the reversal potential was near zero and the inward conductance (36 pS) was larger than the outward conductance (17 pS). In excised inside-out patches the channels showed rectification in the presence of 5 mM Mg2+ on the cytoplasmic side but not in Mg(2+)-free solution. Inward currents were also obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
55
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 22 publications
11
55
0
Order By: Relevance
“…Ion selectivity of the 19-pS gp K ir also supported high preference for K ϩ over Na ϩ or Cl Ϫ (data not shown). These current measurements indicate that the observed channels were K ϩ selective with significant Rb ϩ permeability, suggesting a divergence from other inwardly rectified K ϩ channels (8,49). (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Ion selectivity of the 19-pS gp K ir also supported high preference for K ϩ over Na ϩ or Cl Ϫ (data not shown). These current measurements indicate that the observed channels were K ϩ selective with significant Rb ϩ permeability, suggesting a divergence from other inwardly rectified K ϩ channels (8,49). (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…With high (100 mM) extracellular (luminal) K ϩ , Mg 2ϩ blocked only outward currents at positive membrane potentials, in agreement with previous results. 8,14 We estimated the apparent K i in the absence of a membrane potential [K i (0)] to be about 5 mM with a voltage dependence (z␦) of approximately 0.6. Earlier studies reported a somewhat lower affinity [K i (0) ϳ 13 mM] and higher voltage dependence (z␦ ϳ 1).…”
Section: Discussionmentioning
confidence: 99%
“…The results are similar to those reported previously. 8,14 Currents with lower (0.2 mM) and higher (5 mM) Mg 2ϩ are also plotted in Figure 1C. Thus, under conditions of high K ϩ in the lumen and negative membrane potentials, physiologic levels of intracellular Mg 2ϩ (assumed to be Ͻ1 mM, see Discussion) will have little effect on currents through ROMK channels.…”
mentioning
confidence: 96%
“…At physiological pH, its pK a of 9.25 dictates that ϳ1.5% of the ammonia is found as NH 3 , whereas the rest exists as NH 4 ϩ , the latter of which absolutely requires membrane transporters or channels to cross the plasma membrane. Although dedicated NH 4 ϩ transport proteins have been identified (6), NH 4 ϩ is, due to its resemblance to K ϩ , in addition transported by a range of K ϩ transporters and channels, such as the Na ϩ /K ϩ -ATPase, the Na ϩ /K ϩ /2Cl Ϫ cotransporter, the K ϩ /Cl Ϫ cotransporter, and inwardly rectifying, voltage-, and Ca 2ϩ -activated K ϩ channels (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The permeability of NH 4 ϩ through K ϩ channels usually amounts to ϳ10 -20% of the permeability of K ϩ (7).…”
mentioning
confidence: 99%